CONTEMPORARY COMICS OF LITHUANIA (1990–2005) - BUGAILIŠKIENĖ, JURGITA (Knygotyra, 2015)
This article analyses and summarizes the contemporary comic books and magazines, released in Lithuania during the year 1990–2005. It includes the original Lithuanian, foreign comics, published in Lithuania and the translations from foreign languages. The main tasks of the article are: to analyse the conception of the comics, to explain the term; to know the comic books and magazines de visu, to make the origins index; to explore the tipology of Lithuanian comics according to the maid index (compare comics genres for different contingent of readers, comics features, reveal the content of comics and their communicating characteristics). There were used document analysis, comparative and the method of questionnaire to get the material for the article. There was set the conclusion, that todays society forms a new look to the comics. Comics become valuable for their ability to sense some sort of ideas and traditions. Comics can be called a medium because of their original form. This form come step by step, from one panel satyrical picture to the series of pictures with one plot. Sequence is one of the leading elements of the comics structure. Entertaining and pleasure comics are the most common in Lithuania. Comics in Lithuania are ascribable to childrens literature. The most popular genres in Lithuania among young readers are: journey-adventure comics, comics about rollicking animals, superhero, action comics, detective and fantastic stories. All this genres belong to the spare time comics tipe. There also are comics for learning and spiritual enlightenment in Lithuania. The young readers are interested in entertaining and game functions of comics. Children read comics because of their humour, because they see the reflection of the society in comics and can actualize their imagination. Comics for children are laconic and clear. They use more pictures than text. Comics completeness is conditioned by reality, the fine arts and literary thing combination. Each of them is knowable through the senses, thinking and imagination.